A review of centralised finance (CeFi) and decentralised finance (DeFi) and its challenges to the lending market. - Abdullah Al Mamoon (ZBW - Leibniz Information Centre for Economics, 2025)
In this work, we systematically analyse the differences and similarities between CeFi (Centralised Finance) and DeFi (Decentralised Finance). Financial technology is rapidly expanding, and large technology firms are making advances in credit markets. The Internet of Value (IOV), with its distributed ledger technology (DLT) as a basis, has developed new types of loan marketplaces. In this paper, we enumerate the prospects & challenges of Centralised Finance (CeFi) lending markets driven by banks and other lending institutes, as well as the benefits of DeFi lending protocols that may support resolving long-standing concerns in the conventional lending landscape. Overall, fintech and big tech credit appear to complement rather than substitute conventional forms of lending. This study provides a comprehensive analysis of the distinctions between CeFi (Centralised Finance) and DeFi (Decentralised Finance) lending. It analyses several aspects including legal considerations, economic factors, security measures, privacy concerns, and market structure. We conclude our study that convergence between centralised finance (CeFi) and decentralised finance (DeFi) can facilitate synergies in the lending market.
Keywords: E5; E51; F30; G23; G32; O33; 330; Blockchain; Decentralized finance; Centralised Finance; Smart contract